Teacher Professional Development in the Digital Era: Challenges and Strategies for Educational Management - Eka Rista Harimurti (Civiliza Publishing, Indonesia., 2026)
Teacher professional development has long been recognized as a crucial component in improving the quality of education and enhancing student learning outcomes. This study aims to analyze teacher professional development in the digital era by identifying the key challenges faced by educators and examining effective strategies for educational management in supporting sustainable professional growth. The research employs a library research method by reviewing and analyzing relevant scholarly literature, including academic journal articles, books, and policy documents related to digital transformation in education and teacher professional learning. The collected data were analyzed using a descriptive–analytical approach to synthesize concepts, compare perspectives, and draw comprehensive insights. The results indicate that teacher professional development in the digital era is constrained by challenges such as limited digital competence, unequal access to technology, and insufficient institutional support; however, these challenges can be addressed through strong educational leadership, the integration of digital tools with pedagogical innovation, collaborative professional learning communities, continuous evaluation, and the cultivation of a culture of lifelong learning.